2019
DOI: 10.1128/jvi.00574-19
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Antisense Protein ASP Is a Transmembrane Protein of the Cell Surface and an Integral Protein of the Viral Envelope

Abstract: The negative strand of HIV-1 encodes a highly hydrophobic antisense protein (ASP) with no known homologs. The presence of humoral and cellular immune responses to ASP in HIV-1 patients indicates that ASP is expressed in vivo, but its role in HIV-1 replication remains unknown. We investigated ASP expression in multiple chronically infected myeloid and lymphoid cell lines using an anti-ASP monoclonal antibody (324.6) in combination with flow cytometry and microscopy approaches. At baseline and in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 58 publications
3
51
1
Order By: Relevance
“…As our results suggest that anti-ASP response is dynamic overtime, a deeper study of the relationship between viremia and the antibody response against ASP would require the analysis of these parameters in plasma sampled from patients at shorter temporal intervals. This could also indicate that the in vivo production of ASP occurs when viral production decreases, contrary to what was suggested by the study of Affram et al (2019), but in line with a previous study which suggested that ASP is rather expressed during the chronical phase than during the acute phase of the disease (Bet et al, 2015). Besides, we recorded an increase in ASPspecific antibody titers during the 2.5 years following enrollment in Pat #20, further suggesting that antibody response to ASP is developed after acute infection.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…As our results suggest that anti-ASP response is dynamic overtime, a deeper study of the relationship between viremia and the antibody response against ASP would require the analysis of these parameters in plasma sampled from patients at shorter temporal intervals. This could also indicate that the in vivo production of ASP occurs when viral production decreases, contrary to what was suggested by the study of Affram et al (2019), but in line with a previous study which suggested that ASP is rather expressed during the chronical phase than during the acute phase of the disease (Bet et al, 2015). Besides, we recorded an increase in ASPspecific antibody titers during the 2.5 years following enrollment in Pat #20, further suggesting that antibody response to ASP is developed after acute infection.…”
Section: Discussioncontrasting
confidence: 72%
“…As suggested by the lack of detection of antibodies targeting ASP in the plasma of HIV-1 controllers in our study, a detectable level of viral replication might be needed to induce a humoral response to ASP. Interestingly, ASP was recently described at the membrane of viral particles released by chronically infected cells following their in vitro reactivation (Affram et al, 2019). If ASP is indeed present at the surface of viral particles in vivo, it might partially explain why we did not detect antibodies against ASP in patients displaying very low or undetectable viral loads.…”
Section: Discussionmentioning
confidence: 73%
“…Such inconsistencies complicate research, because OLGs may play key roles in the emergence of new viruses. For example, in human immunodeficiency virus-1 (HIV-1), the novel OLG asp within env is actively expressed in human cells ( Affram et al, 2019 ) and is associated with the pandemic M group lineage ( Cassan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…ASP RNA is derived from the 3′LTR and has been shown to recruit the polycomb group repressive complex 2 (PRC2) to the HIV-1 5′LTR promoter, resulting in repressive epigenetic modifications, i.e., increased H3K27me3 and reduced RNAPII occupancy at the promoter (Zapata et al, 2017 ). A recent study by Affram et al demonstrated that ASP is located in the nucleus of latent myeloid and lymphoid cell lines but translocates to the cytoplasm and cell surface upon stimulation with PMA (Affram et al, 2019 ). Further, ASP co-localized with gp120 on the cell surface and was observed in cell-free HIV-1 particles.…”
Section: Block and Lock Strategiesmentioning
confidence: 99%